Determine the effectiveness of the integrated use of traditional and non-traditional means of physical rehabilitation at the initial degree of exogenous obesity in women first mature age - Юрченко [Olga Yurchenko], Ольга Евгенівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The program of physical rehabilitation for the main and control groups in the initial degree of exogenous obesity in women first mature age. The methods of the study, were used during the research on the effectiveness of the proposed program. The results obtained during the initial and follow-up survey of women. Based on the analysis of the results justified the use of the proposed program for the initial degrees of exogenous obesity in first mature age women with complex use of traditional and non-traditional means of physical rehabilitation. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->